2022
DOI: 10.1093/mr/roac089
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of baricitinib for rheumatoid arthritis in Japanese clinical practice: 24-week results of all-case post-marketing surveillance

Abstract: Objectives To assess safety and effectiveness of baricitinib treatment for rheumatoid arthritis (RA) in real-world clinical practice. Methods This ongoing all-case post-marketing surveillance study (starting September 2017) includes all patients with RA treated with baricitinib in Japan. Safety and effectiveness (disease activity) were assessed for 24 weeks. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 39 publications
10
18
2
Order By: Relevance
“…This retention rate is aligned with rates reported by real-world studies conducted in Japan. The 6-month retention rate was 86.5% in a Japanese multicenter registry in 113 patients with RA, more than half of whom were previously treated with tsDMARDs [ 18 ], and 75.4% in a post-marketing surveillance study that included 4731 patients with RA treated with baricitinib [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This retention rate is aligned with rates reported by real-world studies conducted in Japan. The 6-month retention rate was 86.5% in a Japanese multicenter registry in 113 patients with RA, more than half of whom were previously treated with tsDMARDs [ 18 ], and 75.4% in a post-marketing surveillance study that included 4731 patients with RA treated with baricitinib [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the frequency of adverse events in real-world data, adverse events were found to have occurred in 26.87%, whereas serious adverse events occurred in 4.29% of patients during a 24-week follow-up in the Japanese cohort (n=4731). In this cohort, where 54% of the patients were 65 years and older, the frequency of serious infection and HZ were 1.90% and 3.09%, respectively (13). In a database study from Italy, it was observed that within 1 year, 13% of patients discontinued treatment due to side effects and it was emphasized that the frequency of discontinuation due to side effects was higher, especially in elderly patients and in the bDMARD-resistant patient group [hazard ratio (HR) 1.03, 95% CI 1.01-1.06; p=0.008 and HR 1.93 95% CI 1.01-3.67; p=0.045, respectively] (12).…”
Section: Safety Datamentioning
confidence: 77%
“…Additionally, elevated alanine aminotransferase and aspartate aminotransferase levels were detected in 1.9% and 1.3% of baricitinib monotherapy recipients, respectively, and it was reported that these elevations in liver function tests were transient in most cases (2,7). However, hepatic dysfunction with a rate of 2.77% during the 24-week follow-up was also reported in a Japanese cohort (13). During the 24-week follow-up in the RA-BEACON study, side effects were reported in 64% of the placebo group, 71% of the baricitinib 2 mg group, and 77% of the baricitinib 4 mg group.…”
Section: Safety Datamentioning
confidence: 78%
See 2 more Smart Citations